Selected black African dramatists South of the Zambezi - Litkie, Celeste Avril (Stellenbosch : University of Stellenbosch, 2011)
244 leaves printed on single pages, preliminary pages and numbered pages 1-234. Includes bibliography, list of appendices. Digitized at 330 dpi black and white PDF format (OCR), using a KODAK i 1220 PLUS scanner.